Evaluating treatment effect on interferon-alpha in female patients with systemic lupus erythematosus: a case-control study - Ruaa Hameed Abdulridha,; Asmaa Mohammed Saud,; Mohammed Hadi Alosami, (Journal of the Pakistan Medical Association, 2024)
a